2019
DOI: 10.1177/2332858419850482
|View full text |Cite
|
Sign up to set email alerts
|

An Efficacy Study of a Digital Core Curriculum for Grade 5 Mathematics

Abstract: The Math Curriculum Impact Study was a large-scale randomized controlled trial (RCT) to test the efficacy of a digital core curriculum for Grade 5 mathematics. Reasoning Mind's Grade 5 Common Core Curriculum was a comprehensive, adaptive, blended learning approach that schools in the treatment group implemented for an entire school year. Schools in the control group implemented their business-as-usual mathematics curriculum. The study was completed in 46 schools throughout West Virginia, resulting in achieveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Technology alone is not enough to lead to significant improvements in learning [59]. Although the technology played a fundamental role, the actual pedagogy and lesson plans were important for allowing the students to develop their knowledge and play a leading role in their learning [60].…”
Section: Discussionmentioning
confidence: 99%
“…Technology alone is not enough to lead to significant improvements in learning [59]. Although the technology played a fundamental role, the actual pedagogy and lesson plans were important for allowing the students to develop their knowledge and play a leading role in their learning [60].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, irrespective of whether teachers assign problems one by one or in bulk, they may choose to select different problem sets for different students, depending on their state of knowledge, or they may choose to assign the same problem sets to every student in the class. There is mounting evidence that individualized assignments of single problem sets can benefit student's long-term learning relative to assigning the same single problem sets to each student (Connor et al, 2007;Ecalle et al, 2021;McDonald Connor et al, 2009;Shechtman et al, 2019). Further investigations that focus on the interaction between assignment policy and individualization, may aid future development of online learning platforms, especially in the face of school closures.…”
Section: Discussionmentioning
confidence: 99%
“…There is an intersection with studies on the effects of CRs (2 studies). These studies mainly aim to identify influential factors that could explain the observed effects (e.g., Shechtman et al, 2019).…”
Section: Research On Students' Use Of Crsmentioning
confidence: 99%
“…• Mathematical achievement: The predominant number of studies in this category investigates the effects of CRs on students' mathematical achievement in general (e.g., Shechtman et al, 2019) or related to a particular content area or competency (e.g., mathematical thinking: Drijvers et al, 2019aDrijvers et al, , 2019badaptive expertise: Sievert et al, 2019). Some studies have a longitudinal perspective, covering a whole school year or even longer periods (e.g., van den Ham & Heinze, 2018), others are carried out as intervention studies over shorter periods.…”
Section: Effectsmentioning
confidence: 99%